To determine which pair shows equivalent expressions, let's simplify each expression.
-
First expression: \(-2(x + 5)\) \[ = -2x - 10 \] So, \(-2(x + 5) = -2x - 10\)
Comparing with: \(2x - 10\) → This is not equivalent.
-
Second expression: \(2x + 10\) \[ = -2(x - 5) \] \[ = -2x + 10 \] So, \(2x + 10 \neq -2(x - 5)\)
-
Third expression: \(-2(x - 5)\) \[ = -2x + 10 \] Comparing with: \(-2x - 10\) → This is not equivalent.
-
Fourth expression: \(-2x - 10\) Comparing with: \(-2(x + 5)\) \[ = -2x - 10 \]
Based on the simplifications, the equivalent expressions are: \[ -2(x + 5) = -2x - 10 \] and \(-2x - 10 = -2(x + 5)\)
Thus, the correct answer is: \(-2(x + 5) = -2x - 10\) and \(-2x - 10 = -2(x + 5)\).